Olmesartan-Induced Enteropathy: An Unusual Cause of Villous Atrophy - Eusébio,Marta (2016)
We report a case of a 63-year-old-man presenting with chronic diarrhea and weight loss while on olmesartan treatment for hypertension. Investigation showed multiple nutritional deficiencies associated with diffuse intestinal villous atrophy. Serologies for celiac disease were negative and other causes of villous atrophy were excluded. Olmesartan as a precipitant agent was suspected and withdrawn. Clinical improvement occurred in days with no need for other therapeutic measures. Follow-up at three months showed clinical remission and almost complete recovery of intestinal atrophy. Olmesartan is an angiotensin receptor blocker commonly prescribed for the management of hypertension. Spruelike enteropathy associated with this drug is a recently described entity with few cases reported. It presents with chronic diarrhea and intestinal villous atrophy and should be included in its differential diagnosis. This case intends to alert clinicians for the possibility of this event in a patient on treatment with this drug.